Overland tourism in the Istanbul to Cairo route:‘real holidays’ or McDonaldised niche tourism? - Sarmento, João (2019)
Since the beginning of the 1990s tourism scholars and academics have been claiming that tourism has changed. By and large the mid-1980s is generally considered the moment when that transformation occurred, or, at least, when it became noticeable. Urry (1990), one of earliest theorists who lead this debate, built an all-inclusive theory which frames the new trends in the tourism industry in the broader context of social transformations in the ‘Late Capitalism’ period, and consequently, tourism has been repeatedly considered to have changed because new forms of post-Fordist (or post-Modern) consumption have emerged [...]